Comparative Analysis of Fully Guided and Free-Hand Orthognathic Surgery: Advancements, Precision, and Clinical Outcomes - Sophia Tsokkou; Ioannis Konstantinidis; Antonios Keramas; Georgios Kiosis; Kanellos Skourtsidis; Danai Alexiou; Georgia-Nektaria Keskesiadou; Sofia Karachrysafi; Theodora Papamitsou; Ioannis Chatzistefanou (Dentistry Journal)
Background/Objectives: Orthognathic surgery has evolved with digital advancements, improving precision and predictability. Traditional free-hand techniques rely on surgeon expertise, often leading to variable outcomes. Fully guided approaches integrate computer-assisted surgery, including virtual surgical planning (VSP), CAD/CAM, and dynamic navigation, enhancing accuracy and efficiency. This review compares these approaches, assessing their impact on surgical accuracy, efficiency, and patient outcomes. Methods: A scoping review was conducted across PubMed, MEDLINE, Scopus, Cochrane Library, and Embase databases, focusing on clinical trials and cohort studies. Key parameters analyzed include surgical precision, operative efficiency, complication rates, and functional/aesthetic results. Results: Fully guided techniques achieve sub-millimetric accuracy with mean length deviations ranging from 1.3 mm to 2.4 mm and mean angular deviations between 2.29° and 3.51°. Moreover, these approaches markedly reduce operative time, averaging between 34 min and 1.7 h, and postoperative complications. Digital tools streamline workflow, improving reproducibility and aesthetic outcomes. Free-hand methods remain cost-effective but require greater surgical expertise, often resulting in longer recovery periods and higher variability. Conclusions: Computer-assisted orthognathic surgery enhances precision and efficiency, outperforming free-hand techniques in accuracy and predictability. While free-hand methods remain viable for simpler cases, fully guided approaches optimize surgical execution. Future research should explore hybrid strategies combining digital precision with manual adaptability to further refine surgical techniques.